2018
DOI: 10.24846/v27i3y201808
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Motives for Using Facebook: A Latent Profile Analysis

Abstract: People use Facebook from a variety of motives and literature is dominated by descriptive statistics and variableoriented approaches (e.g., regression). The aim of this paper is to extend previous research by adopting a person-oriented approach (i.e., LPA-latent profile analysis) and examine whether profiles of motivation can be identified. Two empirical studies were performed engaging Romanian university students (557 and 550, respectively). The LPA and mclust package version 5.3 were used to identify groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The results of LPA yielded the presence of four profiles, overall low motives, overall medium motives, overall high motives, and escapist addiction and novelty motives. Consistent with previous research on motivations for using social media ( Cristescu and Balog, 2018 ), the current study revealed the former three profiles reflecting different levels of motivations: overall low, medium, and high. It is notable that the current study also yielded a fourth profile (namely the ‘escapist addiction and novelty motives profile’), which was characterized by high scores in escapist addiction and novelty, but low scores in socially rewarding self-presentation and trendiness.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of LPA yielded the presence of four profiles, overall low motives, overall medium motives, overall high motives, and escapist addiction and novelty motives. Consistent with previous research on motivations for using social media ( Cristescu and Balog, 2018 ), the current study revealed the former three profiles reflecting different levels of motivations: overall low, medium, and high. It is notable that the current study also yielded a fourth profile (namely the ‘escapist addiction and novelty motives profile’), which was characterized by high scores in escapist addiction and novelty, but low scores in socially rewarding self-presentation and trendiness.…”
Section: Discussionsupporting
confidence: 90%
“…The labeling of the profiles is based on the terminology of previous studies on motives for using Facebook profiles (e.g., Cristescu and Balog, 2018 ). Figure 1 shows the different profiles and their means for each TikTok use motive subscale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation